Asymmetric transfer effects among real output, energy consumption, and carbon emissions in China. (1st October 2020) - Liu, Hong; Wang, Chang; Wen, Fenghua
Abstract: This study aims to investigate nexus among China's real output, energy consumption, and carbon emissions from 1971 to 2014. We use a nonlinear autoregressive distributed lag model to examine asymmetric transfer effects among the variables. The findings indicate that the asymmetry effect exists in the relationship among the variables in both the long and short term. Positive and negative shocks of energy consumption and carbon emissions have shown different effects on real output in sign and magnitude. Furthermore, energy consumption and carbon emissions have shown different patterns of influence on real output. In the long run, the decrease in carbon emissions has no significant impact on real output, while the decrease in energy consumption will lead to an increase in real output. In the short run, the negative shock in energy consumption in the previous periods is positively linked to real output, it means the decrease in energy consumption will lead to a decrease in real output. If the government proposes energy-conservation policies, the economic growth will be hampered in the short term but promoted in the long term. The results of this study have clear and important implications for devising energy-conservation and emission-reduction policies in China. Highlights: We empirically investigate the asymmetric nexus among real output, carbon emissions and energy consumption in China. The bounds tests suggest presence of long-run cointegration relationship among the variables. Asymmetry effect is found in the variable's nexus in both long-run and short-run. Energy consumption and carbon emissions have shown different patterns of influence on the real output. Government should be very cautious to set energy-conservation and emission-reduction policies in China.